The Role of Gratitude and Social Support in Life Satisfaction in Online Motorcycle Drivers - Finola Randu Galintias; Mujidin, Mujidin (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2021)
Every job has an impact on workers, one of the impact is whether or not their life satisfaction increases. This study aims to reveal the life satisfaction of online drivers influenced by gratitude and social support. In other words, the aim of this study is to find out how great the role of gratitude and social support on life satisfaction for online drivers (Ojol). The data collection method is simple random sampling or in other words, it is looking for subject randomly and not having special characteristic. Supporting instruments used to reveal this goal are through the gratitude scale, social support scale and life satisfaction scale. The samples are 100 online drivers in Yogyakarta. The responses that received were multiple diverse so that the result of this study refer to a conclusion that there is a role of gratitude and social support on life satisfaction in online drivers (Ojol). Statistically, the significant value is 0.000 < 0.01. In addition, the R square value of 0.527 means that there is about 52.7% contribution of gratitude and social support to life satisfaction. The contribution of these two predictors illustrate that having high life satisfaction will have a positive impact such as working well, being friendly, getting positive feedback from customers, being able to give meaning to life more positively, developing optimally and having good psychological well-being. Suggestions for the next research is to describe more deeply about the gratitude of online drivers and other supporting factors.